Complete Genome Sequence of Xanthomonas Siphophage Samson - Clark, Sabrina (Microbiol Resour Announc, 2019)
The Xanthomonas genus includes many Gram-negative plant-associated bacteria. Here, we report a virulent Xanthomonas siphophage called Samson. A siphophage isolated from sewage, Samson contains a 43,314-bp genome with 58 predicted genes. Samson has high nucleotide identity with Pseudomonas phage PaMx42.